COATING METHODS IN GUIDED BONE REGENERATION PROCEDURES: A LITERATURE REVIEW - Sukarno, M. Faiz Faz; Fathurrahman, Helmi; Sunnah, Tahta Danifatis; Hutami, Islamy Rahma (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: The key to the success of implant placement lies in having an adequate alveolar ridge, yet bone loss in the alveolar ridge can occur due to various factors such as periodontal disease, trauma, tumors, and systemic diseases. One technique that can be used to address alveolar bone damage is guided bone regeneration. This study aims to explore and identify coating methods that can be applied to resorbable and non-resorbable membranes in the context of GBR.Method: The research methodology employed is a literature review. The literature sources were searched through PubMed, Scopus, and the Cochrane Library using the Population, Intervention, Comparison, and Outcome (PICO) method. The review analyzed a total of 30 articles, categorized based on the types of membranes and coating methods used. A narrative literature review approach was utilized in writing the review.Result: This literature review analyzed 30 articles. Thirteen coating methods were applied to resorbable membranes, and three coating methods to non-resorbable membranes.Conclusion: Based on the findings of the literature review, the following conclusions can be drawn: (1) Coating methods are applied to overcome the limitations of both resorbable and non-resorbable membranes in the context of GBR. (2) Dip-coating is a commonly used method for both types of membranes in GBR. (3) Dip-coating demonstrates improved mechanical strength and proven enhancement of osteogenic properties, accelerating the bone healing process in GBR. (4) Coating methods can be combined to address the limitations of both resorbable and non-resorbable membranes in GBR procedures.